Student anxieties and future implications for the library - Sinnasamy, J.; Karim, N.H.A. (2014)
The purpose of this paper is to explore anxieties inherent in students which can hinder the optimal use of library resources, services, and facilities. The instruments used were the Malay translated versions of LAS, FLCAS,and PRCA-24. The study was carried out among final year undergraduates at a public university in Malaysia. The findings revealed that communication anxiety in students correlated with Library Staff Barriers, Library Services Barriers, Library Resources Barriers, Affective Barriers, and Internet Services Barriers. Foreign language anxiety correlated with Library Staff Barriers, Library Services Barriers, and Affective Barriers. The implications for the library is that students who are anxious using a foreign language and have difficulty communicating with others will be unlikely to make full use or demand services from the library. While it is difficult to extricate the multifarious dimensions, to be aware of other anxieties manifesting as library anxiety must be acknowledged and acted upon by librarians.